Respuesta :
ANSWER
The factors are
[tex](2x - 9) \: \: and \: \: (x + 6).[/tex]
EXPLANATION
The given expression is
[tex]2 {x}^{2} + 3x - 54[/tex]
This is a quadratic trinomial.
We need to factor this by splitting the middle term.
We know that,
[tex]a=2, b=3,c=-54[/tex]
So
[tex]ac = - 108[/tex]
Two factors of -108 that sums up to 3 is
[tex]12 \: and \: 9[/tex]
We now split the middle term to obtain,
[tex]2 {x}^{2} + 3x - 54 = 2 {x}^{2} + 12x - 9x - 54[/tex]
We factor to obtain,
[tex]2 {x}^{2} + 3x - 54 = 2x( x + 6) -9( x + 6)[/tex]
We factor further to obtain,
[tex]2 {x}^{2} + 3x - 54 = ( x + 6) (2x-9)[/tex]
Hence the factors are
[tex](2x - 9) \: \: and \: \: (x + 6)[/tex]
The correct answers are option A and F
The factors are
[tex](2x - 9) \: \: and \: \: (x + 6).[/tex]
EXPLANATION
The given expression is
[tex]2 {x}^{2} + 3x - 54[/tex]
This is a quadratic trinomial.
We need to factor this by splitting the middle term.
We know that,
[tex]a=2, b=3,c=-54[/tex]
So
[tex]ac = - 108[/tex]
Two factors of -108 that sums up to 3 is
[tex]12 \: and \: 9[/tex]
We now split the middle term to obtain,
[tex]2 {x}^{2} + 3x - 54 = 2 {x}^{2} + 12x - 9x - 54[/tex]
We factor to obtain,
[tex]2 {x}^{2} + 3x - 54 = 2x( x + 6) -9( x + 6)[/tex]
We factor further to obtain,
[tex]2 {x}^{2} + 3x - 54 = ( x + 6) (2x-9)[/tex]
Hence the factors are
[tex](2x - 9) \: \: and \: \: (x + 6)[/tex]
The correct answers are option A and F